2016
DOI: 10.1186/s13020-016-0075-z
|View full text |Cite
|
Sign up to set email alerts
|

Chinese medicines in the treatment of experimental diabetic nephropathy

Abstract: Diabetic nephropathy (DN) is a severe micro vascular complication accompanying diabetes mellitus that affects millions of people worldwide. End-stage renal disease occurs in nearly half of all DN patients, resulting in large medical costs and lost productivity. The course of DN progression is complicated, and effective and safe therapeutic strategies are desired. While the complex nature of DN renders medicines with a single therapeutic target less efficacious, Chinese medicine, with its holistic view targetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 97 publications
(68 reference statements)
0
7
0
Order By: Relevance
“…DBD has been used as a clinical agent against renal dysfunction for more than 1, 000 year in China [ 10 15 ]. In recent years, several investigations have highlighted its beneficial action on diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DBD has been used as a clinical agent against renal dysfunction for more than 1, 000 year in China [ 10 15 ]. In recent years, several investigations have highlighted its beneficial action on diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…DBD was shown to enhance bone regeneration [ 6 ], attenuate pulmonary fibrosis [ 7 ], stimulate proliferation of T-lymphocytes proliferation [ 8 ], and treat ailments by phosphorylating estrogen receptors [ 9 ]. Therapeutic effects of DBD in kidney-related disorders such as renal anemia and diabetic nephropathy have been recently reported [ 10 15 ]. DBD was shown to induce erythropoietin expression via hypoxia-inducible factor-1α signaling pathway in the kidneys [ 16 ], to alleviate renal damage in streptozotocin-induced diabetic rats [ 10 ], and to reduce adriamycin-induced nephropathy in rats [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The total saponins in DPT can decrease UA production by inhibiting the activities of XO and ADA. Liu (2019) reported that total pangolin saponin could effectively adjust the mRNA and protein levels of URAT1, GLUT9, OAT1, and OAT3 and promote renal urate excretion in PO-induced HUA mice.…”
Section: Other Drugsmentioning
confidence: 99%
“…Polyphenolic compounds are widely found in plants and provide several pharmacological properties, including antidiabetic effects [ 66 , 67 , 68 ]. Although not focused in the present discussion, it is important to recognize that the Chinese medicine has demonstrated the efficacy of several natural products that have been used in the treatment of DM as reviewed elsewhere [ 69 ]. In this subsection, the main polyphenols with potential antidiabetic activity investigated by us as well as others will be addressed.…”
Section: Potential Of Natural Products With Antioxidant Effects Fomentioning
confidence: 99%